Management of Workforce Recruitment in an Islamic Perspective : Practices and Principles - Wahyuddin, Wahyuddin; Nur Alim Mu’min, Muh Dian; Parmitasari, Rika Dwi Ayu; Syariati, Alim (Economos : Jurnal Ekonomi dan Bisnis, 2024)
In the era of globalisation and intense competition, workforce recruitment is one of the key factors in improving the quality of employees and improving organisational performance. In practice, workforce recruitment is one of the important aspects of human resource management in an organisation. In the context of an Islamic perspective, the recruitment and selection process must be carried out in accordance with Islamic principles and values. This research aims to explore recruitment and selection practices in the labour market in an Islamic perspective. This research is a research using the library research method. The results of this study show that in Islamic organisations, alignment of workforce needs with job descriptions and specifications is essential to ensure compliance with Islamic values. Integration orientation plays an important role in developing employees who are not only technically competent, but also have a strong understanding of Islamic values and commitment to the organisation. Regular and open evaluation and feedback can help organisations improve the recruitment and selection process on an ongoing basis, so as to attract and select the best candidates that match the needs of the organisation, as well as provide a positive experience for applicants and the recruitment team. By applying the principles of fairness, equality and legal compliance, organisations can build recruitment and selection processes that are fair, transparent and non-discriminatory.